2020
DOI: 10.1111/and.13850
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effects of methylene blue on testicular damage induced by cisplatin in rats

Abstract: Cisplatin (CP) is a chemotherapeutic drug widely used for the treatment of different types of solid tumours (Wang & Lippard, 2005). However, clinical uses of CP are restricted due to severe side effects like nephrotoxicity, ototoxicity, hepatotoxicity and neurotoxicity (Florea & Büsselberg, 2011). Also, the toxic effect of CP on the reproductive system is well established (Howell & Shalet, 2005). Studies have revealed that the consumption of CP leads to several tissue injuries and biochemical changes in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Similarly, Salem Values are expressed as means ± SD. Significant differences as compared with the Control group at a P < 0.05, Significant differences as compared with the CP group at b P < 0.05 Jourabi et al, 2021). Decreased testosterone levels caused by CP may disrupt the spermatogenesis process and thus may cause male infertility.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Salem Values are expressed as means ± SD. Significant differences as compared with the Control group at a P < 0.05, Significant differences as compared with the CP group at b P < 0.05 Jourabi et al, 2021). Decreased testosterone levels caused by CP may disrupt the spermatogenesis process and thus may cause male infertility.…”
Section: Discussionmentioning
confidence: 91%
“…According to the findings of our study, it is estimated that the decrease in serum testosterone level caused by CP application may be related to the decrease in Leydig cell number as a result of increased apoptosis in Leydig cells. Because testosterone secretion is directly related to Leydig cell function and number (Gholami Jourabi et al., 2021). Decreased testosterone levels caused by CP may disrupt the spermatogenesis process and thus may cause male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that CP treatment reduced testicular weight and volume (Altındağ & Meydan, 2021; Gholami Jourabi et al, 2021; Mesbahzadeh et al, 2021). Consistent with previous studies, it is estimated that this decrease in testicular weight in the present study may be due to the decrease in testicular cell number and seminiferous tubule damage after CP application, because testicular weight is primarily related to testicular cell number and damage.…”
Section: Discussionmentioning
confidence: 99%
“…According to these findings of our study, it is estimated that the decrease in the number of Leydig cells caused by CP may have decreased the testosterone level. Because the main function of Leydig cells is to synthesize and secrete testosterone, the decrease in CP‐induced cell numbers and dysfunction of these cells causes a decrease in testosterone levels (Gholami Jourabi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In many pathologic states of the reproductive system, for example, varicocele, testicular torsion, and drug toxicity caused (e.g., due to cisplatin), oxidative stress plays a remarkable role in tissue damage such as damage to the epithelium of the seminiferous tubules, and the biochemical changes such as reduced testosterone level. The destructive effects of ROS are mediated by alterations of protein structures, DNA damage, and lipid oxidation (Dolatkhah et al, 2020; Gholami Jourabi et al, 2021; Koksal et al, 2012). Studies have shown that the destructive effects are reduced in the presence of enzymatic and non‐enzymatic antioxidants.…”
Section: Introductionmentioning
confidence: 99%